AVALIAÇÃO DA COMPOSIÇÃO CORPORAL, DENSIDADE MINERAL ÓSSEA E RISCO DE FRATURAS EM PACIENTES PÓS-BARIÁTRICOS TARDIOS UTILIZANDO O DXA E A FERRAMENTA FRAX® - Calcing, Aline (2020)
Overweight affects up to two thirds of the world population and obesity represents one of the main challenges for global public health. Bariatric surgery is indicated for patients with failed clinical treatment and promotes rapid weight loss with improvement in comorbidities, however, it produces profound changes in body composition and is still controversial in view of the consequences and decline in bone density. The present study is characterized by being cross-sectional, having occurred from August 2018 to December 2019, the sample consisted of patients selected by convenience from a private bariatric surgery service. Those over 18 years of age who underwent the Rouxen- Y bypass technique for more than 18 months, with weight stability for at least 6 months, were included. All study participants had detailed information about the work and were included by signing the informed consent form. Through a structured interview, clinical data, laboratory tests, bone mineral density and body composition were collected through DXA, and application of the FRAX® tool to analyze the risk of fractures. The objective of the study was to analyze body composition, bone mineral density and risk of fractures in patients. Twenty-six patients participated in the research, most of them female, with an average of % of excess weight loss of 97,6%. Patients in the groups with the highest % of excess weight loss had lower Fat Mass Index (P=0,006) and Appendicular Lean Mass (P=0,016), lower android/gynoid rate (P=0,023) and lower visceral fat (P=0,008). Values of osteopenia and osteoporosis were found in the sample, supplementation of vitamin D, calcium and multivitamin for the majority of the sample was discontinued, patients with lumbar bone mineral density classified as below the control population had higher values of calcium (P=0,027) and highest % of excess weight loss. There was a correlation between lumbar bone mineral density below the control population and high calcium values (P=0,027), as well as higher values of % of excess weight loss (P=0,004). There was a significant correlation between the possibility of hip fracture and lower lumbar bone mineral density (P=0,018) and lower femur bone mineral density (P=0,002). The sample showed satisfactory results in the % of excess weight loss. Body composition values show that the surgery did not harm the patients' lean mass and that it improved aspects of fat mass and visceral fat, however the high rate of % of excess weight loss and the discontinued use of supplementation may have altered the lower lumbar bone mineral density of the sample and this interfered with the probability of developing hip fracture.